176k views
0 votes
WILL GIVE BRIANLIEST!! plato

WILL GIVE BRIANLIEST!! plato-example-1
User Akotian
by
4.1k points

1 Answer

4 votes

Answer:

A.
A = (1)/(2)\cdot \sqrt{(x_(2)^(2)+y_(2)^(2))\cdot (x_(2)^(2)+y_(2)^(2))}

Explanation:

From Geometry, we know that the area of the triangle (
A) is equal to:


A = (1)/(2)\cdot b\cdot h (1)

Where:


b - Base.


h - Height.

By Pythagorean Theorem, we derive expressions for the base and the height of triangle. That is:


h = \sqrt{(-x_(1)-0)^(2)+(y_(1)-0)^(2)}


h = \sqrt{x_(1)^(2)+y_(1)^(2)} (2)


b = \sqrt{(x_(2)-0)^(2)+(y_(2)-0)^(2)}


b = \sqrt{x_(2)^(2)+y_(2)^(2)} (3)

By (2) and (3), we expand (1):


A = (1)/(2)\cdot \sqrt{(x_(2)^(2)+y_(2)^(2))\cdot (x_(2)^(2)+y_(2)^(2))}

Hence, correct answer is A.

User MirkoBanchi
by
5.3k points